Impact of Insurance Status on Outcomes in Patients With Placenta Accreta Spectrum [A173]. (May 2022) - Hussein, Nada; Rigaud, Rachelle A.; Edwards, Sara; Harrison, Rachel; Holmgren, Calla
Abstract : INTRODUCTION: Placenta accreta spectrum (PAS) leads to significant maternal morbidity and mortality. We hypothesized that women with public insurance diagnosed with PAS have increased complications compared to those with private insurance. METHODS: This was a retrospective cohort study drawn from the Healthcare Utilization Project–National Inpatient Sample database from across the U.S. between January and December 2018. Inclusion criteria were those with an antepartum diagnosis of PAS, and we compared those with private to those with public insurance. The primary outcome was a composite of surgical complications, including organ/vascular injury or need for repair, ileus or bowel obstruction, IR intervention, or pelvic hematoma. The secondary outcomes were each individual component of the composite. Groups were compared via t tests, chi-square, and logistic regression analyses. RESULTS: A total of 1, 401 women were eligible for analysis; of these, 709 had public insurance. Women with public insurance were more likely to be Black or Hispanic, of lower socioeconomic status, obese, tobacco users, and be diagnosed with placenta percreta (all P <.05). Those with public insurance had higher rates of the primary composite outcome of any surgical complication (17.0% versus 12.5%, P =.040). However, multivariable logistic regression showed no statistically significant difference in the composite of surgical complications (aOR, 1.19; 95% CI, 0.77–1.84) when adjusted for race, obesity, tobacco use, prior cesarean deliveries, and income, although women with public insurance were 2.5 times more likely to have an ileus or small bowel obstruction (aOR, 2.52; 95% CI, 1.05–6.05). CONCLUSION: In this cohort of women with PAS, insurance status was associated with higher rates of ileus or bowel obstruction.